Engineering empires : - Marsden, Ben (Palgrave Macmillan, 2005)
Engineers are empire-builders. James Watt, Isambard Kingdom Brunel, Robert Stephenson and a host of lesser known figures worked to build and expand personal and business empires of material technology founded on and sustained by durable networks of trust and expertise. In so doing these engineers and their heirs also became active agents of political and economic empire. Indeed, steamships, railways and electric telegraph systems increasingly complemented one another to form what one early twentieth-century telegraph engineer aptly termed 'our most powerful weapon in the cause of Inter-Imperial Commerce'. This book provides a fascinating exploration of the cultural construction of the large-scale technologies of empire.